Species Diversity and Cave-Bat Conservation Efforts in Aoma Village, Wolasi District -Southeast Sulawesi - Amirullah, Amirullah; Bakkareng, Sitti Wirdhana Ahmad; Risnaldi, La Ode Fabir (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
Indonesia a tropical country that remains warm all year, has the largest biodiversity. This study aims to determine the diversity of bats of the order Microchiroptera in Rau Cave, Wolasi, Conservation (Protected) Forest area, around Aoma Village, South Konawe Regency. Data collection was carried out using a mist net measuring 6 x 2 meters which were stretched in front of the mouth of the cave at 16.00 before the bats came out looking for food and harvested at 06.00-0.700. The trapped bats were identified using the Sulawesi Bat and its role in the health sector, and other relevant references. The results showed that there were 26 trapped bats consisting of  5 species, namely Rhinolopus arcuatus (Prok Bruk Sulawesi), Hipposideros ater (Barong gauld), Dobsonia viridis (Kubu Hijau), Miniopterus australis (Tomosu australi) and Hipposideros dinops (Barong horsfield). The species found consisted of 2 families, namely the families Rhinolopidae and Hipposideridae, and consisted of 2 genera, namely the genera of Dobsonia and Miniopterus. The diversity index shows a value (H') = 0.986, which indicates a low category in diversity and a Margalef wealth index (R) of 0.26. It is necessary to conserve plant species both for eating insects and for food sources for Microchiroptera bats in their feeding ground